1999
DOI: 10.1016/s0022-2275(20)32148-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective modification of apoB-100 in the oxidation of low density lipoproteins by myeloperoxidase in vitro

Abstract: Oxidative modification of LDL may be important in the initiation and/or progression of atherosclerosis, but the precise mechanisms through which low density lipoprotein (LDL) is oxidized are unknown. Recently, evidence for the existence of HOCl-oxidized LDL in human atherosclerotic lesions has been reported, and myeloperoxidase (MPO), which is thought to act through production of HOCl, has been identified in human atherosclerotic lesions. In the present report we describe the formation of 2,4-dinitrophenylhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Although the oxidation of biological molecules by MPO is commonly attributed to generation of HOCl (5,(12)(13)(14)(15)(16)(17), we observed that MPO-catalyzed oxidation of LDL in vitro produced a much different pattern of DNPH-reactive products than was observed from reaction of LDL with reagent HOCl (9,10). Oxidation of LDL with HOCl produced a diverse array of DNPH-reactive peptides, with little indication of selectivity.…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…Although the oxidation of biological molecules by MPO is commonly attributed to generation of HOCl (5,(12)(13)(14)(15)(16)(17), we observed that MPO-catalyzed oxidation of LDL in vitro produced a much different pattern of DNPH-reactive products than was observed from reaction of LDL with reagent HOCl (9,10). Oxidation of LDL with HOCl produced a diverse array of DNPH-reactive peptides, with little indication of selectivity.…”
mentioning
confidence: 73%
“…Similar oxidations were conducted at 37 Њ C in the presence or absence of MPO by addition of 16, 40, 160, 400, 1,000, or 4,000 nmol of HOCl, either added at 1.5 min intervals in 10 separate aliquots or as a single bolus dose, corresponding to an HOCl:apoB-100 molar ratio of 10, 25, 100, 250, 625, and 2,500, respectively. Fifteen minutes after initiation of the respective oxidations, the samples were reacted with DNPH, the protein was precipitated, delipidated, and digested with trypsin, and the tryptic peptides were analyzed by HPLC, as we have described previously (9).…”
Section: Oxidation Of Ldl By Mpomentioning
confidence: 99%
See 3 more Smart Citations